Vórtices BPS na eletrodinâmica de Maxwell-Higgs com acoplamento nªo mínimo quebrando as simetrias de CPT e de Lorentz - Mota, Alexsandro Lucena (2014)
The first studies on Lorentz-violating BPS vórtices were accomplished within the framework of the Standard Model Extension (SME). Specifically, it was studied the effects of the Lorentz violation in the vortex solutions presented in the Maxwell-Higgs electrodynamics. The formation of vórtices was also analyzed in (1+2)-dimensional models obtained by dimensional reduction of the SME Abelian sector. Among the several effects of the Lorentz violation we can mention: the control of both the amplitude as the width of the vortex, magnetic field reversion, magnetic flux quantization with explicit dependence on the Lorentz-violating coefficients. In this dissertation we study the existence of topological BPS vórtices in a Maxwell-Higgs model in which the covariant derivative is modified by the addition of a CPT-odd term, which breaks the CPT- and Lorentz symmetry due to the presence of a vectorial background. The interaction generating a set of self-dual or first-order equations includes a potential jφj4 and a derivative coupling j@iφj4. Although the self-dual equations are very different of those belonging to the usual MaxwellHiggs model, the new vortex solutions behave just like the Aharonov-Nielsen-Olesen ones, but the mass scale depends explicitly on the Lorentz-violating coefficient.